A proposed library program supporting the developmental reading program of the Esteban Abada High School - Mata, Celia C. (1980)
Schools of today place increasing emphasis on effecting closer ties or cooperation between the school library and the other departments in the school to make teaching more effective to enable the students to cope with the many changes that have occurred and have been taking place. While educators on various subject areas continue to implement new thrusts for the benefit of the students, librarians must constantly reexamine and reassess their stock of materials and services to determine their effectiveness to the schools they serve.